2010
DOI: 10.1039/b915843j
|View full text |Cite
|
Sign up to set email alerts
|

FLAG tagging by CuAAC and nanogram-scale purification of the target protein for a bioactive metabolite involved in circadian rhythmic leaf movement in Leguminosae

Abstract: We report a stepwise FLAG-tagging strategy for the purification of target proteins for bioactive metabolites. This method realizes the microscale purification and identification of target protein from as few as 1 x 10(5) differentiated cells. Using this method, we isolated and identified MetE as a cytosolic target protein of potassium isolespedezate, a metabolite controlling plant nyctinasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…5a) (20). We planned to identify the target protein of 8 using the molecular probe (21). As mentioned earlier, a major problem with this approach is non-specific binding; however, we were unable to use the enantiodifferential approach because this compound and its enantiomer exhibit exactly the same bioactivity.…”
Section: Identification Of Lof Target Protein Using Click Chemistrymentioning
confidence: 99%
“…5a) (20). We planned to identify the target protein of 8 using the molecular probe (21). As mentioned earlier, a major problem with this approach is non-specific binding; however, we were unable to use the enantiodifferential approach because this compound and its enantiomer exhibit exactly the same bioactivity.…”
Section: Identification Of Lof Target Protein Using Click Chemistrymentioning
confidence: 99%
“…We synthesized molecular probe 14 with the tosyl group as a reacting group and azide as a pre-tag group. 15,16) An additional aromatic group was inserted in the middle of the linker part to enhance maltase inhibition by hydrophobic interaction. The intestinal glucosidase inhibitory activity of 14 was estimated to be IC 50 ¼ 22 mM against maltase and IC 50 > 100 mM (25% at 100 mM) against sucrase.…”
mentioning
confidence: 99%
“…[14][15][16] As a first set of derivatives, phenolic hydroxyl and amine group modified derivatives were synthesized and tested for their sucrase and maltase inhibitory activity to determine whether can be utilized to attach a functional group (Experimental procedures; see Biosci. Biotechnol.…”
mentioning
confidence: 99%
“…was used for CuAAC coupling with fluorescein isothiocyanate (FITC)-alkyne (16) 16) to give FITC-labeled COR (17) in almost quantitative yield (Scheme 1). Further bioorganic studies using 17 will be reported in elsewhere.…”
Section: à9mentioning
confidence: 99%